Analysis Of The Influence Of Organizational Commitment And Job Satisfaction On Turn Over Intention In Hospitality Industry - Roy Setiawan; Balla Wahyu Budiarto; Rif'ah Shafwah; Nurul Hasanah; Loso Judijanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to examine if work satisfaction and organizational commitment variables have an additive effect on employee turnover intention. The sample size for this study was 200 contract workers. This study's sampling methodology is nonprobability. Purposive sampling was the technique utilized, and there were 100 samples in all. In this study, questionnaires and interviews were employed to collect the data. An ordinal scale was employed as the measurement system for the questionnaire. Using descriptive statistics, data quality testing, traditional assumption testing, and hypothesis testing with SPSS, the collected data will next be examined and evaluated. The following conclusions can be drawn from the findings of the data testing that was done on the issue utilizing multiple linear regression tests: On the likelihood of leaving a job, job satisfaction has a large beneficial impact. The intention to leave the company is significantly impacted negatively by organizational commitment. The intention to leave the company is significantly influenced by both job satisfaction and organizational commitment at the same time.